Gambaran Motivasi Warga Belajar Mengikuti Pelatihan Menjahit di PKBM Nurul Hidayah Kecamatan Kamang Magek Kabupaten Agam - Jumia Sesti; Syuraini Syuraini (Universitas Negeri Padang, 2018)
This research is motivated by the success of citizens learning in training to open their own businesses, such as receiving wages for orders from suppliers and neighbors. This study aims to see (1) the intrinsic motivation of the learning population in training (2) the extrinsic motivation of the learning population in the training. The type of this research is descriptive quantitative with the circulation of 20 people studying. The sample from this study is the total population of 20 people. Data collection techniques use questionnaires (questionnaires) and data collection tools are a list of statements. The data analysis technique uses the percentage formula. The results of the study showed that (1) the intrinsic motivation of the learning population in attending the training was high, (2) the extrinsic motivation of extrinsic learning residents in training was high.Keywords: Motivation, Training